2021
DOI: 10.2196/25495
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in Digital Health Services: Protocol for a Concept Analysis

Abstract: Background Due to the rapid digitalization of health care, leadership is becoming more complex. Leadership in digital health services is a term that has been used in the literature with various meanings. Conceptualization of leadership in digital health services is needed to deliver higher quality digital health services, update existing leadership practices, and advance research. Objective The aim of this study is to outline a concept analysis that aim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The multitude of concepts demonstrates the complexity of remote leadership in the context of health care. The diversity of concepts applied in analyses of health-care leadership in digital contexts and needs for more rigorous definition and standardisation of terms have been previously recognised (Laukka et al , 2021). Also, the concept analysis of the remote leadership in health care would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…The multitude of concepts demonstrates the complexity of remote leadership in the context of health care. The diversity of concepts applied in analyses of health-care leadership in digital contexts and needs for more rigorous definition and standardisation of terms have been previously recognised (Laukka et al , 2021). Also, the concept analysis of the remote leadership in health care would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed protocol for this concept analysis has been published (Laukka et al, 2021 ). We used the concept analysis model by Walker and Avant ( 2019 ), a frequently used tool in health care settings (Nuopponen, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…An information specialist helped develop the initial and final search strategies. An initial limited search of MEDLINE (Ovid) was undertaken on 19 October 2020 as part of a concept analysis protocol (Laukka et al, 2021 ). On 31 November 2020, four databases (MEDLINE (Ovid), Scopus, CINAHL (EBSCO) and ProQuest (ABI/INFORM)) were searched using indexing and keywords with a limit of 10 years (Appendix S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Physicians with administrative roles may use digital technologies and also collaborate in diverse ways. Leadership in digital health services is thought to require interprofessional and intersectoral collaboration [ 85 ]. It is also suggested that leaders in health care may generally view the effects of digitalization differently and more positively than professionals (Kaihlanen, unpublished data, June 2022).…”
Section: Discussionmentioning
confidence: 99%